The Austro–Prussian War of 1866 - الجـــنابي هـديل عباس حمد (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
The Austro-Prussian War of 1866 marked a crucial turning point in the history of Central Europe. It was a pivotal conflict between the Kingdom of Prussia and the Austrian Empire over leadership of the German Confederation and the process of German unification. The war arose as a result of escalating political and military tensions between the two powers, with the goal of dominance within the German states. Prussia was led by Chancellor Otto von Bismarck, who pursued a pragmatic policy focused on strengthening Prussia’s position in Europe by neutralizing internal opponents and enhancing military and technological power. The Prussian army was distinguished by its efficient organization and use of railways and advanced weapons, giving it a tangible strategic advantage. In contrast, the Austrian Empire suffered from poor coordination and leadership, as well as poor weapons and military planning. The war resulted in a decisive Prussian victory in the Königgrätz (Königsbrücke) War, which marked the major turning point in the conflict. The Austrian defeat led to the signing of the Treaty of Prague, which reshaped the political map of Germany. Austria was excluded from the North German Confederation, paving the way for Prussia to unify Germany under its leadership.